Combined Effect of Nitrogen Fertilizer Application and High Temperature on Grain Quality Properties of Cooked Rice - Xu, Yanqiu; Guan, Xianyue; Han, Zhanyu; Zhou, Lujian; Zhang, Yan; Asad, Muhammad A. U.; Wang, Zhaowen; Jin, Rong; Pan, Gang; Cheng, Fangmin (Frontiers in Plant Science, 2022)
Ambient temperature and nitrogen (N) fertilizer are two of the most important factors that affect rice grain quality. However, less information has been available on the interactive effect of N fertilizer and ambient temperature on grain quality under stressful high temperature (HT). In this article, the effects of panicle N fertilizer, ambient temperature, and their interaction on starch composition, particle size distribution of starch granules, starch physicochemical properties, and storage protein accumulation in milled grains were investigated to clarify the potential role of panicle N fertilizer topdressing in regulating rice grain quality under stressful HT by using a two-factor experiment of three N levels in combination with two temperature regimes. Results showed that appropriate application of panicle N fertilizer could attenuate the adverse effect of HT during grain filling on milling quality and chalky occurrence to some extent, particularly for the effective alleviation of HT-induced decrease in milling quality. However, the topdressing of panicle N fertilizer tended to enhance starch gelatinization enthalpy (ΔH) and its setback viscosity in HT-ripening grains, with the simultaneous decrements in the number and surface area proportions of smaller starch granules under the higher N fertilizer in combination with HT exposure. The effects of higher nitrogen fertilizer and HT exposure on total protein content and gluten composition of grains were additively increased. Hence, the topdressing of panicle N fertilizer exacerbated HT-induced deterioration in cooking and eating quality, rather than alleviating the negative impact of HT exposure on the palatability of cooked rice.